Calibrating the Yield Strength of Archean Lithosphere Based on the Volume of Tonalite-Trondhjemite-Granodiorite Crust - Gunawardana, Prasanna M.; Morra, Gabriele; Chowdhury, Priyadarshi; Cawood, Peter A. (Frontiers in Earth Science, 2020)
Lithospheric yield stress is a key parameter in controlling tectonic processes. Using high resolution, 2D numerical modelling, we calculate the yield stress for a range of conditions appropriate to the early-to-mid Archean Earth, including hotter mantle potential temperatures and Moho temperatures. We then evaluate its effect on generating tonalite-trondhjemite-granodiorite (TTG) crust and benchmark the results against the preserved igneous rock record. Our results indicate that lithospheric yield stress values lower than the present-day values (i.e. ≤ 100 MPa) can generate TTG volumes similar to those preserved in the rock record. The models further highlight the dominance of lithospheric dripping in producing the Archean TTGs. Large volumes of TTG melts form within the thin, tail portions of the drips as these regions are more efficiently heated by the enclosing hotter mantle. In contrast, only limited melting occurs within the thickened parts of lithosphere as they are significantly weak and cannot sustain crustal thickening for long time periods, resulting in its removal via dripping. This study, therefore, reaffirms the dominance of non-plate tectonic mechanisms in producing TTGs under the conditions that operated on the hotter Archean Earth.